2022
DOI: 10.2174/1389557521666210831152511
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plant Metabolites on Coronaviruses: A Comprehensive Review Focusing on their IC50 Values and Molecular Docking Scores

Abstract: : Coronaviruses have caused worldwide outbreaks in different periods. SARS (severe acute respiratory syndrome), was the first emerged virus from this family, followed by MERS (Middle East respiratory syndrome) and SARS-CoV-2 (2019-nCoV or COVID 19), which is newly emerged. Many studies have been conducted on the application of chemical and natural drugs for treating these coronaviruses and they are mostly focused on inhibiting the proteases of viruses or blocking their protein receptors through binding to amin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…In fact, among the 211 reviews here found ( Figure 1 ), 85 cite one or more of Beck’s articles. Notably, one earlier recapitulative publication from Beck’s group [ 72 ] has been cited in 15 reviews or books since the beginning of the pandemic [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ], including a widely read one [ 78 ] that is itself cited by 790 articles, based on Scopus.com. Unfortunately, this recapitulative paper contains inconclusive and contradictory results, and was indeed subsequently revised by the same group.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, among the 211 reviews here found ( Figure 1 ), 85 cite one or more of Beck’s articles. Notably, one earlier recapitulative publication from Beck’s group [ 72 ] has been cited in 15 reviews or books since the beginning of the pandemic [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ], including a widely read one [ 78 ] that is itself cited by 790 articles, based on Scopus.com. Unfortunately, this recapitulative paper contains inconclusive and contradictory results, and was indeed subsequently revised by the same group.…”
Section: Resultsmentioning
confidence: 99%
“…The IC50 value (the concentration at which 50% of enzyme activity is lost), molecular docking score, and binding energy are all parameters used to determine a metabolite's ability to inhibit a specific virus. Polyphenols, alkaloids, terpenoids, organosulfur compounds, saponins, essential oil, saikosaponins, lectins, nicotianamine, etc., are examples of secondary plant metabolites (Farshi et al, 2022). Usual compounds derived from tulsi and neem possess more binding efficacy against SARS-CoV-2 targets tangled in viral attachment and replication for the treatment of SARS-CoV-2 infections (Shrestha et al, 2022).…”
Section: Various Mechanisms Of Phytochemicals Againstmentioning
confidence: 99%
“…The extracts with IC50 values between 0.01 and 0.05 mg/mL and 0.5 to 0.1 mg/mL are considered to have strong and intermediate antioxidant activity, respectively. Antioxidant activity is considered low in extracts with an IC50 value of 0.1 mg/mL or higher (Farshi et al 2022). As shown in Table 4, showed that the extract of P. porphyrophyllum (EtOH), B. balsamifera (EtOAc and EtOH), and N. acuminatissima (EtOH) have strong antioxidant activity according to the categories above.…”
Section: Antioxidant Activitymentioning
confidence: 99%